Gambaran Asupan Energi, Zat Gizi Makro Dan Status Gizi Remaja di SMP N 14 Kota Bengkulu Tahun 2022 - Meta Irwanda; Desri Suryani; Arie Krisnasary; Yandrizal Yandrizal (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Background: The nutritional status of adolescents has a very big influence in realizing quality human resources in the future. Nutritional status is the state of the body which is an illustration of what is eaten daily. Objective: This study was to determine the description of energy intake, macronutrients and nutritional status of adolescents in SMP N 14 Bengkulu City. Methods: This is a descriptive study conducted in May 2022 with a sample of 69 people, the sampling technique used is the simple random sampling method. Nutrient intake using food recall 3 x 24 hours and then the data is processed by the nutrisurvey program, data analysis is univariate. Results: The study showed that the nutritional status of adolescents was not malnourished, undernourished 6 people (8.7%), good nutrition 50 people (72.5%), over nutrition 9 people (13%) and obesity 4 people (5.8 %). The energy intake of adolescents in the mild deficit category was 21 people (30.43%), the most protein was in the normal category, 31 people (44.93%), the most fat was in the more category, 32 people (46.4%) and the most carbohydrates were in the heavy deficit category, 61 people. (88.41%).